Synthesis of a 2,5-Diazabicyclo[2.2.1]heptane-Derived α,β-Diamino Acid - Ivon, Yevhen M.; Tymtsunik, Andriy V.; Komarov, Igor V.; Shishkin, Oleg V.; Grygorenko, Oleksandr O. (Synthesis, 2015)
The synthesis of optically pure (1S,4S)-2,5-diazabicyclo[2.2.1]heptane-1-carboxylic acid starting from easily available ‘chiral pool’ l-4-hydroxyproline is reported. A tandem Strecker reaction–intramolecular nucleophilic cyclization (STRINC) sequence was used as the key synthetic step for the first time to prepare a diamino acid. Careful examination of the side products obtained in the STRINC step allowed the suggestion of a mechanistic explanation for the observed facts and optimization the yield of the aminonitrile precursor. The reported scalable synthesis opens the way to use the diamino acid as a branch point in peptides and as a building block in drug discovery.
Keywords: amino acids; molecular rigidity; Strecker reaction; nucleophilic cyclization; bicyclic compounds